Geopolitics and global strategy: Making moneyunder anarchy - Blake, Daniel J.; Jandhyala, Srividya; Li, Quan (Wiley, 2026)
Research Summary Multinational firms conduct cross-border trade and investment in a world of anarchy, where nation-states must secure their survival in the absence of a world government. We develop a geopolitical-economic order (GEO) framework to argue that the extent of geopolitical competition incentivizes states to create one of two types of economic order: a market-based order built on laissez-faire and mutually beneficial voluntary exchanges, and a state-based order focused on state power and government intervention in the economy. Different orders shape the institutional environment for firms' cross-border activities in unique ways, leading to distinct sources of competitive advantage and market and non-market strategies. When the status quo level of geopolitical competition is disrupted, the prevailing and future state–market order becomes uncertain, forcing firms to prioritize strategic flexibility. Managerial Summary Countries exist within an international system with no world government to safeguard their interests. To ensure their nations security, governments prioritize geopolitics. When governments perceive a greater threat to their countries and heightened geopolitical competition, they are more willing to intervene in the affairs of multinational enterprises (MNEs), thereby increasing transaction costs. However, when geopolitical competition is more muted, governments may constrain themselves to promote cross-border investments by lowering barriers to entry, limiting discrimination against foreign firms, securing MNEs' property rights, and aligning regulations. Thus, geopolitics can foster two distinct types of economic “order.” In a transitory state, however, firms cannot determine the prevailing state–market relationship. Knowing which order a firm operates in is crucial for managers because different orders reward different strategies and sources of competitive advantage.
Keywords: 59 Ciencia Política::5901 Relaciones internacionales; ODS 16 - Paz, justicia e instituciones sólidas; anarchy; geopolitical risk; geopolitics; global strategy; multinational firms; state–market order